Incidence of back pain in track and field athletes: A transversal study - Mondoni, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Back pain is better localized at the lumbar spine and sciatica can become if not prevented or cured. The purpose of this research is to identify if the incidence of back pain is more common in athletes who practice different disciplines in Track and Field (throwing, jumping, speed and middle distance race), compared to persons who do not practice this sport. MATERIALS AND METHODS: The groups examined are: track and field group (TaFg), mean age 23.5 years, comprising 160 athletes (m and f) and control group (CP), mean age 26.5 years, comprising of 80 persons (m and f) that do not practise TaF. All subjects were given an anonymous questionnaire to assess the incidence of back pain in physical activity. RESULTS: The data collected showed that 65% of throwers and jumpers suffer from back pain and that 68% have never suffered from sciatica and has never stopped the pain. The Taf group suffers most from low back pain (60.56%), compared with the CP (39.44%) and both groups said they were not suffering from sciatica pain and it never stopped the pain. The 76.92% of TaFg said they did not suffer from back pain while filling out the questionnaire and 60% said they had back pain over the last 30 days and the throwers said to suffer more back pain than other athletes. The TaFg said to suffer back pain once every 6 months, especially the jumpers and throwers have reported suffering from back pain more than once a month.. Confronted with the CP, showed that the TaFg undergoes more medical visits for low back pain resulting in rehabilitative therapy. In the TaFg 69% said they had never suffered back pain before starting the competitive activity, 74% of the `test sample` thinks that the sporting activity has been affected quite to develop of back pain, 58% said they suffer from back pain during training before the competitive season. CONCLUSIONS: The research shows that in TaF increasing incidence of low back pain, especially in males. The disciplines that cause more back pain are the throws and jumps. Comparing the TaFg with the CP, we can say that competitive athletes suffer more back pain than the CP. The throwers and jumpers said they frequently suffer from back pain, more often than once a month. From our observations we found that the TaFg underwent further medical examinations and treatments (drugs or otherwise), especially the throwers and jumpers, compared to the CP. The last part of the research, dedicated only to TaFg, it was found that subjects had never suffered from back pain before the race and think that has influenced the start of racing onset of back pain, especially for the sprinters, jumpers and throwers, also claimed to suffer more back pain during athletic training in the competitive season.